Exploratory Study of Epidermis, Basement Membrane Zone, Upper Dermis Alterations and Wnt Pathway Activation in Melasma Compared to Adjacent and Retroauricular Skin - Cavalcante Esposito, Ana Claudia [UNESP]; Brianezi, Gabrielli [UNESP]; Souza, Nathalia Pereira de [UNESP]; Bartoli Miot, Luciane Donida [UNESP]; Miot, Helio Amante [UNESP] (Korean Dermatological Assoc, 2020)
Background: Melasma is a chronic acquired focal hyper-melanosis which pathogenesis has not been fully elucidated. Classical pathophysiologic studies have analysed the affected and perilesional areas, but little is known about the status of sun-protected skin, which is subjected to the same endogenous and genetic factors. Objective: To assess the histological characteristics of melasma compared to adjacent and retroauricular skin. Methods: Skin samples were collected from 10 female from: melasma, perilesional area and retroauricular. The samples were stained (haematoxyl in-eosin, periodic acid-Schiff, Fontana-Masson, picrosiri us red, toluidine blue and Verhoeff), immunolabelled for CD34 and Wnt1. The data from the skin sites were analysed simultaneously by a multivariate model. Results: Melasma skin exhibited noteworthy stratum corneum compaction, greater collagen heterogeneity, solar elastosis, higher number of mast cells, basement membrane zone (BMZ) damage, Wnt1 expression, pendulum melanocytes, higher cell ularity and vascular proliferation at the superficial dermis. Stratum corneum compaction, collagen heterogeneity and BMZ abnormalities were variables associated to melasma that not follow a continuum through retroauricular to adjacent skin. Mast cell count was the variable that disclosed correlation with the most other abnormalities as well as had the greater contribution in the multivariate model. Conclusion: In addition to melanocyte hyperactivity, melasma skin exhibits alterations in the epidermal barrier, upper dermis and BMZ, which differ from the adjacent sun-exposed skin and retroauricular skin, indicating a distinct phenotype, rather than a mere extension of photoageing or intrinsic ageing. Mast cells appear to play a central role in the physiopathology of melasma.
Keywords: Basement membrane; Dermis; Epidermis; Melanosis